The economy of Puerto Rico : restoring growth - Collins, Susan Margaret; Bosworth, Barry, 1942-; Soto-Class, Miguel A. (San Juan, P.R. : Center for the New Economy ; Washington, D.C. : Brookings Institution Press, 2006)
In this innovative new book, economists from U.S. and Puerto Rican institutions address a range of major policy issues affecting the islands economic development. To frame the current situation, the contributors begin by assessing Puerto Ricos past experience with various growth policies.
Contents -- Foreword -- Preface -- Acknowledgments -- Introduction and Summary -- Economic Growth -- Labor Supply and Public Transfers -- Why Don't More Puerto Rican Men Work? The Rich Uncle (Sam) Hypothesis -- Education and Economic Development -- The Climate for Business Development and Employment Growth -- Assessing Puerto Rico's Fiscal Policies -- Financing Economic Development -- Trade Performance and Industrial Policy -- Restoring Growth: The Policy Options -- Contributors -- Index
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Puerto Rico -- Economic policy; Puerto Rico -- Economic conditions -- 1952-; Economic history; Histoire économique.; Porto Rico -- Politique économique.; Porto Rico -- Conditions économiques -- 1952-; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; POLITICAL SCIENCE -- Political Economy; Economic history; Economic policy; Puerto Rico; Since 1952